2013
DOI: 10.1002/anie.201302319
|View full text |Cite
|
Sign up to set email alerts
|

High‐Molecular‐Weight Regular Alternating Diketopyrrolopyrrole‐based Terpolymers for Efficient Organic Solar Cells

Abstract: The recent significant increase in power conversion efficiency (PCE) of polymer-fullerene solar cells largely originates from the successful development of new electron donor polymers. The donor-acceptor (D-A) or push-pull design, where electron-rich and electron-deficient units alternate along the copolymer chain-is commonly used to tune the HOMO and LUMO energy levels and the optical band gap of these polymers. [1,2] While structure-property relationships for energy levels are well-established, these are les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
331
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(340 citation statements)
references
References 24 publications
8
331
1
Order By: Relevance
“…It was found that low molecular mass of PBDTTPD resulted in poor efficiency mostly because of the phase separation of the polymer and fullerene derivative and the formation of PC 70 BM-enriched domains, which was avoided in the case of the high-M n polymer. That study 56 and several similar publications 57,58 have demonstrated that the correlation between the BHJ solar cell performance and the molecular mass of the donor polymer may appear to be a promising method for optimization of the solar cell morphology and design of highly efficient structures.…”
Section: Iii1a Basics Of Solar Cellsmentioning
confidence: 69%
“…It was found that low molecular mass of PBDTTPD resulted in poor efficiency mostly because of the phase separation of the polymer and fullerene derivative and the formation of PC 70 BM-enriched domains, which was avoided in the case of the high-M n polymer. That study 56 and several similar publications 57,58 have demonstrated that the correlation between the BHJ solar cell performance and the molecular mass of the donor polymer may appear to be a promising method for optimization of the solar cell morphology and design of highly efficient structures.…”
Section: Iii1a Basics Of Solar Cellsmentioning
confidence: 69%
“…Owing to its electron deciency, DPP is known for providing access to small band gap polymers with high efficiencies in photovoltaic devices and ambipolar charge transport in eld-effect transistors. [1][2][3][4][5][6] TPD is slightly less electron decient, which results in wide to medium band gap materials. [7][8][9][10] Traditionally, semiconducting copolymers with a push-pull conguration only use the combination of one donor and one acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, two electron rich (or electron poor) building blocks are combined with one electron poor (or electron rich) building block. 2,[11][12][13][14][15] Incorporation of the different co-monomers in the polymer can be achieved in a regular or a (semi)random fashion. One of the principal reasons for using multiple components in the synthesis of semi-conducting polymers is that it can lead to broadening of their absorption spectra, which can be benecial for the harvesting of photons in a photovoltaic cell.…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the class of organic photovoltaics (OPV) has particular advantages in terms of aesthetics, flexibility, and cost and mainly aims at portable or wearable consumer goods and building/automotive integration [1][2][3][4][5]. OPV device efficiencies have recently made a huge leap forward, reaching~10% for polymerand small-molecule-based solution-processed bulk (single) heterojunction devices [6][7][8][9][10][11][12][13][14][15][16][17]. Nevertheless, some issues concerning cost, efficiency, and reliability still need to be resolved for OPV to become an economically viable technology.…”
Section: Introductionmentioning
confidence: 99%